2019
DOI: 10.1136/bmjhci-2019-000012
|View full text |Cite
|
Sign up to set email alerts
|

Patient perceptions and interactions with their web portal-based laboratory results

Abstract: BackgroundThe movement to improve patient-centred care, combined with the development of user-friendly technology has led to the spread of electronic patient portals (EPP). Little research has examined the effects of providing patients with access to their laboratory results on their healthcare and health behaviours.ObjectiveThe purpose of this study was to gain insight into the use of EPPs, understand why patients use EPPs to access their laboratory results and explore its impact on their health.MethodSemistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(71 citation statements)
references
References 16 publications
3
68
0
Order By: Relevance
“…Improved access to patient information and records was reported as a benefit following EHR/PHR implementation [17,34,37,45,48,56,65,69,75,90,91,99,101,128,147,150,153]. Nurses perceived that increased accessibility enhanced their job performance [20,28].…”
Section: Accessibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Improved access to patient information and records was reported as a benefit following EHR/PHR implementation [17,34,37,45,48,56,65,69,75,90,91,99,101,128,147,150,153]. Nurses perceived that increased accessibility enhanced their job performance [20,28].…”
Section: Accessibilitymentioning
confidence: 99%
“…Better communication between patients and providers was reported as a benefit following the implementation of EHRs/PHRs [32,34,38,42,44,69,86,87,102,134,146,147,153]. Physicians recognized the value of being able to share patient-centered information with patients using EHRs [34,143], while clinicians perceived that new communication channels such as messaging through EHRs should improve communication between patients and providers [45].…”
Section: Communicationmentioning
confidence: 99%
“…Many of the studies [ 47 , 68 , 77 , 80 , 82 , 100 , 101 , 109 - 112 , 114 ] have explored patient experiences with access to patient portals and subsequently access to their own medical information. All of the studies reported that users were highly satisfied with the access, and in one study, 97% of survey respondents stated that they would definitely or probably recommend the portal to other clients and families [ 110 ].…”
Section: Resultsmentioning
confidence: 99%
“…EPPs are websites that allow patients to view laboratory results, refill prescriptions, manage appointments, and communicate with their providers 3 . Posited benefits of EPPs include work efficiency gains for providers and enhanced engagement with health matters, including self‐care, for patients 3‐5 . However, accessing abnormal or ambiguous test results via an EPP can cause anxiety for patients and lead to an increased number of clinical follow‐up visits 3‐5 .…”
Section: The Case Factsmentioning
confidence: 99%
“…EPPs are websites that allow patients to view laboratory results, refill prescriptions, manage appointments, and communicate with their providers 3 . Posited benefits of EPPs include work efficiency gains for providers and enhanced engagement with health matters, including self‐care, for patients 3‐5 .…”
Section: The Case Factsmentioning
confidence: 99%